Fractional anisotropy in white matter hyperintensities is linked to associative memory performance: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Haddad, Seyyed Mohammad Hassan; Scott, Christopher J.M.; Ozzoude, Miracle; Holmes, Melissa F.; Arnott, Stephen R.; Nanayakkara, Nuwan D.; Kwan, Donna; Tan, Brian; Casaubon, Leanne; Mandzia, Jennifer; Sahlas, Demetrios J.; Saposnik, Gustavo; et al.
Abstract: Background: Alzheimer's disease pathology commonly coexists with cerebrovascular anomalies, suggesting a strong association between cerebrovascular lesions and cognitive performance. While different types and locations of cerebrovascular lesions such as strokes and white matter hyperintensities (WMHs) may interfere with various cognitive domains, these associations are not thoroughly understood. The most common approach to characterize and evaluate cerebral lesions is with structural neuroimaging. However, diffusion tensor imaging (DTI) can assess the microstructural integrity of cerebral tissue lesions, which may directly impact neuronal communication and consequently cognitive function. This study examines the variation in DTI metrics within different cerebrovascular lesions and their association with cognition in people with cerebrovascular disease (CVD). Method: The variation of DTI metrics in 10 different cerebral tissues and lesions was examined in 152 subjects (aged 55‐85 years, 32% female) with CVD, (evidenced by an ischemic stroke event documented by MRI or CT, with a modified Rankin score 0‐3) available from the Ontario Neurodegenerative Disease Research Initiative (ONDRI). Fractional anisotropy (FA) and mean diffusivity (MD) were measured using an established DTI processing pipeline from 3 Tesla DTI images (32 directions, b=1000 s/mm 2 ). Cerebral tissue lesion masks were obtained by semi‐automated segmentation of the structural T1 ‐weighted images to calculate average DTI metrics in each region of interest (ROI). In addition, FA in normal appearing WM (NAWM) and WMHs were correlated with MoCA score (measure of gross cognition), Rey Auditory Verbal Learning Test Long‐Delayed Recall score (measure of episodic memory), Trail Making Test‐Part B in seconds (measure of executive function), and Face‐Name Associative Memory Test score (measure of associative memory). Result: Figure 1 shows a T1 ‐weighted anatomical image, corresponding tissue mask identifying vascular lesions, and corresponding MD and FA maps. Fig. 2 provides the average FA and MD in different cerebral tissues/lesions. FA within WMHs was found to be significantly correlated with Face Name Associative Memory Test score (p‐value<0.01, r=0.23, Fig. 3) after Bonferroni correction. No other significant associations were identified. Conclusion: Considerable heterogeneity in DTI metrics was observed between cerebral tissues and lesions. Importantly, the structural integrity within WMHs also associated with higher associative memory performance.